Opowieść o sile jedności (Natałka Babina, "Bodaj Budka") - Zywert, Aleksandra (Acta Neophilologica, 2022)
The present article discusses the latest novel by Natalka Babina, Бодай Будка [Bodai Budka, 2019] – the first Ukrainian-language novel written and published in Belarus. The writer continues her analysis concerning the problem of identity of Belarusians (touched upon earlier in the novel Town of Fish [2007]) and at the same time fights against the stereotype of a Belarusian as a “soul slave”. This time, Babin’s attention is focused on language as the decisive factor in the process of personality self identification. Therefore, the problems of the multilingualism of Belarusians (with special regard to the Ukrainian language), cultural memory, and the (essentially hostile) hegemony of the Russian language are brought to the fore.